A study on the influence of hull wake on model scale cavitation and noise tests for a fast twin screw vessel with inclined shaft. (August 2018) - Tani, Giorgio; Viviani, Michele; Villa, Diego; Ferrando, Marco
The study of ship underwater radiated noise is nowadays a topic of great and largely recognized importance. This is due to the fact that in the last decades, the problem of the impact of anthropogenic noise on marine life has been addressed with higher emphasis, giving rise to different efforts aimed to the analysis of its effects on different organisms and, in parallel, to means for the reduction of shipping noise. In this context, attention is focused on the propeller noise, which, in cavitating conditions, may represent the most important noise source of the ship. The propeller noise has been studied for long time with different approaches. One of the most effective approaches is represented by model scale testing in cavitation tunnels or similar facilities. Despite having been adopted for several years, radiated noise experiments in model scale are usually affected by significant scale effects and technical issues. One of these aspects is represented by the correct modelling of the propeller inflow; different techniques are adopted, depending on the facility, in order to reproduce a certain target wake. One of the main problems is to define this target wake, which should in principle coincide with the ship wake; as it is well known, it is usually derived from model scale towing tank measurements, with the necessity for the prediction of the full-scale wake field. Starting from the outcomes of a previous work on the influence of different approaches for the prediction of the full-scale wake field for a single screw ship, in this work, attention is focused on the case of a fast twin screw vessel, analysing the different issues which may be connected to this hull form.